Short Communication: Behavioral study on Anguilla bicolor using a modified trap design at laboratory scale - Aristi Dian Purnama Fitri; Herry Boesono; Faik Kurohman; Bogi Budi Jayanto; Desca Estiyani Dewi; Agus Sabdono (Society for Indonesian Biodiversity, 2019)
Abstract. Fitri ADP, Boesono H, Kurohman F, Jayanto BB, Dewi DE, Sabdono A. 2019. Short Communication: Behavioral study on Anguilla bicolor using a modified trap design at laboratory scale. Biodiversitas 20: 2159-2165. The information on the behavioral juvenile eels Anguilla bicolor is urgently needed as basic design of selective and sustainable traps. The objectives of this study were to find out and analyze the behavioral pattern and characteristics of A. bicolor elvers in the modified and non-modified eel traps. The test organism, A. bicolor juvenile eels with 150-170 mm in length, were obtained from Segara Anakan waters, Cilcacap. The 2 trap designs, which were modifications of the 450 mm long PVC eel trap, with and without the addition of bait hole, were used in this study. All experiments were carried out in the laboratory of Fish Behavior, Diponegoro University, Semarang, Indonesia. The eel characters and response time were recorded using a handy camera that placed on top of the aquariums. The results indicated six types of A. bicolor behavior in response to the modification of eel traps. Moreover, the trap design with an additional hole on the wall, with or without bait, was proven to have no significant effect on the response time. While trap without column and bait possessed the fastest response time at which elver penetrated to the trap (p-value ? 0.05). Furthermore, these results indicated that A. bicolor elver gained entrance into the trap, in an attempt to take shelter.